Peptide Receptor Radionuclide Therapy for Gastroenteropancreatic Neuroendocrine Tumors - El-Haddad, Ghassan (Digestive Disease Interventions, 2019)
Peptide receptor radionuclide therapy (PRRT), a targeted form of systemic radiotherapy allowing the delivery of radionuclides directly to tumor cells, has been used for more than three decades in the treatment of advanced neuroendocrine tumors (NETs) exhibiting high levels of somatostatin receptors. Recently, 177Lu-DOTATATE, a radiolabeled somatostatin analog, was approved by the US Food and Drug administration for the treatment of somatostatin receptor-positive gastroenteropancreatic neuroendocrine tumors (GEP-NETs) in adults. Early phase I and II studies have shown the benefits of PRRT, but it was the NETTER-1 trial (a large-scale randomized multicenter trial for progressive well-differentiated advanced or metastatic somatostatin receptor-positive midgut carcinoid tumors) that provided high-level evidence of improved overall response rate, and progression-free survival compared with long-acting octreotide. In this article, we will discuss the evolution, clinical applications, and implementation of PRRT, as well as potential future strategies to enhance its clinical efficacy in the treatment of GEP-NETs.
Keywords: peptide receptor radionuclide therapy; NETTER-1; neuroendocrine tumor; pancreas; carcinoid